The tropopause at southern extratropical latitudes: Argentine operational rawinsonde climatology - Bischoff, S.A. (2007)
Argentine operational rawinsonde records spanning a 30-year period (1968-1997) were used to study the climatology of the tropopause from the subtropics to the southern mid-latitudes, approximately along the 60°W meridian. The thermal tropopause annual cycle as well as its variability was analyzed at three sites: Resistencia (RES), Ezeiza (EZE), and Comodoro Rivadavia (CRD). Single and double tropopause observations were studied, given the comparatively frequent occurrence of double tropopause events at all three sites. The tropopause behavior at RES and CRD is distinct, whereas at EZE it shows a winter evolution similar to the one at CRD and a summer evolution closer to the one at RES, in agreement with the annual evolution of the subtropical jet. The tropopause evolution is discussed under the light of the dynamic climatology of southern South America. In the presence of double tropopause events and in terms of potential temperature, it should be noted that the upper tropopause temperature is close to the 380 K isentropic, i.e. the tropical tropopause layer. Moreover, the lower tropopause and single tropopause events are fairly close together, i.e. coincident with the lowermost stratosphere. Considering previous research and results from the present analysis, a definition of Extratropical Tropopause Layer (ExTL) is introduced in this work. It is proposed that the lowermost stratosphere should be regarded as the ExTL. Copyright © 2006 Royal Meteorological Society.